James G. Blaine : architect of empire - Crapol, Edward P. (Biographies in American foreign policy, 2000)
"Sor Juana Ines de la Cruz (1648-1695) wrote poetry, prose, and plays and is considered the greatest of Mexican women writers." "Traditionally, scholars have attributed only one complete play to Sor Juana, but in 1989 Guillermo Schmidhuber discovered a lost play, The Second Celestina, which he proved conclusively to be Sor Juana's earliest comedia, co-authored with Agustin Salazar y Torres. His critical study is the first dedicated exclusively to the secular plays and the first to confirm Sor Juana's authorship of three dramatic pieces. Combining literary history and criticism, Schmidhuber explores the life and originality of Sor Juana's dramas and helps elucidate her enigmatic genius."